Targeting the G-quadruplex as a novel strategy for developing antibiotics against hypervirulent drug-resistant Staphylococcus aureus - Maria Sultan; Maria Razzaq; Joohyun Lee; Shreyasi Das; Shrute Kannappan; Vinod Kumar Subramani; Wanki Yoo; Truc Kim; Hye-Ra Lee; Akhilesh K. Chaurasia; Kyeong Kyu Kim (Journal of Biomedical Science)
Abstract Background The rapid emergence of multiple drug-resistant (MDR) bacterial pathogens and the lack of a novel antibiotic pipeline pose a serious threat to global healthcare. The limited number of established targets further restricts the identification of novel antibiotics to treat life-threatening MDR infections caused by Staphylococcus aureus strains. Therefore, novel targets for developing antibiotics are urgently required. In this study, we hypothesized that the G-quadruplex (G4)-binding ligands can be used as novel antibiotics as their binding can possibly downregulate/block the expression of vital genes. Methods To test this, first we screened the antibiotic properties of representative G4-binding ligands against hypervirulent and MDR S. aureus USA300 and determined the in vitro and in vivo antibacterial activity; and proposed the mechanism of action by applying various microbiological, infection, microscopic, and biophysicochemical techniques. Results Herein, among screened G4-binding ligands, N-methyl mesoporphyrin IX (NMM) showed the highest antibacterial activity against S. aureus USA300. NMM exhibited a minimum inhibitory concentration (MIC) of 5 μM against S. aureus USA300, impacting cell division and the cell wall by repressing the expressions of genes in the division cell wall (dcw) gene cluster. Genome-wide bioinformatics analysis of G4 motifs and their mapping on S. aureus genome, identified the presence of G4-motif in the promoter of mraZ, a conserved master regulator of the dcw cluster regulating the coordinated cell division and cell wall synthesis. Physicochemical assessments using UV–visible, circular dichroism, and nuclear magnetic resonance spectroscopy confirmed that the G4-motif present in the mraZ promoter formed an intramolecular parallel G4 structure, interacting with NMM. In vivo reporter followed by coupled in vitro transcription/translation (IVT) assays confirmed the role of mraZ G4 as a target interacting NMM to impose extreme antibacterial activity against both the gram-positive and -negative bacteria. In-cell and in vivo validation of NMM using RAW264.7 cells and Galleria mellonella; respectively, demonstrated that NMM exhibited superior antibiotic activity compared to well-established antibiotics, with no observed cytotoxicity. Conclusions In summary, the current study identified NMM as a broad-spectrum potent antibacterial agent and elucidated its plausible mechanism of action primarily by targeting G4-motif in the mraZ promoter of the dcw gene cluster.